Boundary object use in cross-cultural software development teams. - Barrett, Michael; Oborn, Eivor (Human Relations, 2010)
This article examines the evolving use of boundary objects in cross-cultural software teams. Our field study of a Jamaican-Indian team examines the use of software specifications and project management tools as boundary objects in facilitating sharing across knowledge boundaries. We examine how and why the role and use of boundary objects may facilitate collaboration across knowledge boundaries at one time and contribute to conflict at other times. We unpack the interacting elements that both facilitate and constrain knowledge sharing, and trigger conflicts at different stages of the software team development. Specifically, we found that the use of boundary objects at transitions involving definitional control and the subsequent redistribution of power/authority may inhibit knowledge sharing. The subsequent reifying of cultural boundaries along with negative stereotyping led to relational conflict, through a process we call culturizing, as cross-cultural differences emerged as problematic for team dynamics. Reprinted by permission of the publisher.